2012
DOI: 10.1111/j.1365-2486.2012.02762.x
|View full text |Cite
|
Sign up to set email alerts
|

Do nitrogen fertilizers stimulate or inhibit methane emissions from rice fields?

Abstract: In rice cultivation, there are controversial reports on net impacts of nitrogen (N) fertilizers on methane (CH ) emissions. Nitrogen fertilizers increase crop growth as well as alter CH producing (Methanogens) and consuming (Methanotrophs) microbes, and thereby produce complex effects on CH emissions. Objectives of this study were to determine net impact of N fertilizers on CH emissions and to identify their underlying mechanisms in the rice soils. Database was obtained from 33 published papers that contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(135 citation statements)
references
References 57 publications
10
119
0
Order By: Relevance
“…Physiologically, the enzymatic similarity of ammonia oxidizers and MOB may result in ammonia oxidation by MOB (Bodelier and Frenzel, 1999), leading to reduced availability of ammonia for ammonia oxidizers. However, previous studies showed that MOB had lower affinity for ammonia than for CH 4 (Banger et al, 2012;Bedard and Knowles, 1989;Yang et al, 2011). Moreover, it has been proposed that ammonia oxidation by MOB occurred only when the ratio of ammonia to CH 4 is higher than 30 in soils (Banger et al, 2012;Bodelier and Laanbroek, 2004;Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically, the enzymatic similarity of ammonia oxidizers and MOB may result in ammonia oxidation by MOB (Bodelier and Frenzel, 1999), leading to reduced availability of ammonia for ammonia oxidizers. However, previous studies showed that MOB had lower affinity for ammonia than for CH 4 (Banger et al, 2012;Bedard and Knowles, 1989;Yang et al, 2011). Moreover, it has been proposed that ammonia oxidation by MOB occurred only when the ratio of ammonia to CH 4 is higher than 30 in soils (Banger et al, 2012;Bodelier and Laanbroek, 2004;Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The tight coupling between nitrogen fertilization and methane emission from rice paddy ecosystems in combination with the significant contribution of these systems to the global methane emission, 15 to 25 % (Bodelier, 2011), has evoked numerous studies focusing on this topic. Recent meta-analysis indicates that the increasing rice biomass by nitrogen fertilization may result in the elevated supply of readily available carbon in support of methanogenesis, stimulating methane emission in paddy fields (Banger et al, 2012). However, opposed to this is a strong body of evidence demonstrating stimulation of methane oxidation by ammonium-based fertilizers in rice 3354 Y. Zheng et al: Interactions between soil methane and ammonia oxidizers soil, leading to reduced methane flux (Bodelier et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…The total N 2 O emissions decreased by 7-38 and 26-42 % in the rice and wheat seasons, respectively, when the conventional N management (300 kg N ha −1 for rice and 180 kg N ha −1 per crop for wheat) changed to optimum N management (225-270 kg N ha −1 for rice and 135-162 kg N ha −1 per crop for wheat). It is likely that more N 2 O was emitted (Mosier et al, 2006) as a result of the additional N made available to the soil microbes through N fertilizer application, which also probably contributed to increased CH 4 emissions (Banger et al, 2013). Strategies that can reduce N fertilization rates without influencing crop yields can inevitably lower GHG emissions (Mosier et al, 2006).…”
Section: Ch 4 and N 2 O Emissions As Affected By Issm Strategiesmentioning
confidence: 99%
“…According to the genome sequence of Methanocellaceae (Erkel et al, 2006), a unique set of genes encoding antioxidant enzymes and oxygen-insensitive fermentation enzymes were found, which probably improved their ability to adapt to alternate dry/wet conditions. Although nitrate nitrogen may compete for electrons, which was crucial for methane production (Lai et al, 2016;Zhu et al, 2016), stimulation of plant growth by nitrate based fertilizers can enhance methane production by increased organic carbon availability for fermenting microbes delivering methanogenic substrates (Banger et al, 2012). Thus, the effects of nitrate nitrogen on methane emission were complicated.…”
Section: Discussionmentioning
confidence: 99%